1998
DOI: 10.1212/wnl.50.6.1761
|View full text |Cite
|
Sign up to set email alerts
|

Tethered cord syndrome in occult spinal dysraphism

Abstract: A significant number (10/22) of children born with occult spinal dysraphism and TC did not develop UMN symptoms during follow-up; neurosurgical correction after the appearance of an UMN sign restored normal neurologic and urinary function in all children; and untethering in children presenting at birth with UMN symptoms resulted in poorer outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 1 publication
0
33
0
Order By: Relevance
“…The surgery is safe and effective, with good long-term neurological results. While most neurosurgeons have recently been operating on spinal lipomas even in the absence of symptoms [1, 2, 3, 4, 6, 7, 8, 9, 10, 28, 34, 47], it is still far from conclusive that prophylactic surgery for asymptomatic conus lipomas is more effective than conservative management [9, 13, 15, 48, 49]. Due to the obvious ethical considerations, the natural history of this clinical condition has not been established with prospective, randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…The surgery is safe and effective, with good long-term neurological results. While most neurosurgeons have recently been operating on spinal lipomas even in the absence of symptoms [1, 2, 3, 4, 6, 7, 8, 9, 10, 28, 34, 47], it is still far from conclusive that prophylactic surgery for asymptomatic conus lipomas is more effective than conservative management [9, 13, 15, 48, 49]. Due to the obvious ethical considerations, the natural history of this clinical condition has not been established with prospective, randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is some literature which sheds light on this topic. Cornette et al[ 37] reported a group of 22 consecutive newborns diagnosed with occult spinal dysraphism associated with low conus. They were treated with an algorithm that reserved surgical untethering only for patients with upper motor neuron dysfunction.…”
Section: Diagnosismentioning
confidence: 99%
“…There does not appear to be a difference in motor improvement rates between pediatric and adult series. Early intervention after symptom development appears to result in a much greater recovery of neurological function, with many patients making full recoveries[ 37, 58]. …”
Section: Surgical Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…In the development process of the central nervous system, the distal spinal cord is abnormally attached to the surrounding tissues, and tethering of the spinal cord interferes with the normal regression process causing damage to the spinal cord as it is stretched and placed under abnormal tension. The release of a tethered spinal cord by sectioning the tethering tissues is a straightforward surgical procedure that can prevent, arrest, or ameliorate neurological deficits [13, 14]. Laboratory studies in animals and observations in human patients show that there is a link between the degree of oxidative metabolic impairment and the severity of neurological deficits in TCS.…”
Section: Discussionmentioning
confidence: 99%